2016
DOI: 10.1016/j.clinthera.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Health Behaviors in Cervical Cancer Survivors and Associations with Quality of Life

Abstract: Purpose Improvement in health behaviors following cancer diagnosis may contribute to better prognosis and well-being. This study examines the prevalence of health behaviors in cervical cancer survivors who have completed treatment, and associations between health behaviors and quality of life (QOL). Methods We recruited 204 women who had completed treatment for cervical cancer to participate in a randomized counseling intervention. Participants provided information on health behaviors (smoking, physical acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 37 publications
1
21
2
Order By: Relevance
“…Therefore, poorer emotional functioning and poorer mental health have been associated with higher FCR [ 17 ]. Concerning factors related to anxiety, Iyer et al [ 29 ] found that CCSs who exercised at least 3 hours per week experienced less depression and anxiety. Furthermore, Kim et al [ 2 ] reported anxiety in CCSs was commonly associated with financial difficulty, poor body image, sexual inactivity, low existential well-being and insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, poorer emotional functioning and poorer mental health have been associated with higher FCR [ 17 ]. Concerning factors related to anxiety, Iyer et al [ 29 ] found that CCSs who exercised at least 3 hours per week experienced less depression and anxiety. Furthermore, Kim et al [ 2 ] reported anxiety in CCSs was commonly associated with financial difficulty, poor body image, sexual inactivity, low existential well-being and insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…12 Health-related behaviors, including smoking, lack of physical activity, and increased alcohol consumption, also contribute to decreased overall survival and quality of life in cervical cancer survivors. As noted by Osann et al, 13 prospective studies have shown that cervical cancer survivors who are smokers have more recurrences than do nonsmokers with significantly shorter overall survival.…”
mentioning
confidence: 81%
“…Iyer et al 13 undertook their study to describe the prevalence of health behaviors, specifically, physical activity, smoking, and alcohol consumption, among cervical cancer survivors, with the ultimate goal of examining the associations between health behaviors and quality of life. Cervical cancer survivors were recruited to participate in a randomized psychosocial by-telephone counseling trial.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A separate domain of surveys concerning CaCx is presented by studies addressing the issues of quality of life (QoL), information needs, sexuality, and other problems in patients with cervical cancer or its precursor, who had undergone the treatment [45][46][47][48][49].…”
Section: Survey As An Instrument To Get Informationmentioning
confidence: 99%